Joint Deformities in Patients of Rheumatoid Arthritis Report of 112 cases from Lahore, Pakistan - ATIYA MAHBOOB, AFLAK RASHEED, MANAAL AFZAAL, ASMA MUNIR, (Journal of Fatima Jinnah Medical University, 2018)
Background : Rheumatoid arthritis is a chronic systemic inflammatory autoimmune disease typically involving joints causing symmetric polyarthritis leading to progressive joint destruction and functional impairment . Objectives: To determine the frequency and pattern of joint deformities in patients with rheumatoid arthritis. Study Design: Descriptive case series. Place and duration of study: Department of Medicine Shaikh Zayed Medical Institute, Lahore from 01- 01- 13 to 30-06-13. Subjects and Methods: Hundred and twelve patients with rheumatoid arthritis of both sexes above fifteen years of age fulfilling the ACR 2010 criteria were evaluated for age, gender and pattern of joint involvement. Results: There were 13 (11.68%) males and 99 (88.4%) female patients, male to female ratio was 1:7.6. 13.4% of the patients were below and 86.6% of the patients were above 30 years of age. Mean age of the patients was 42.38 ±10.7 years. Thirty-nine patients (34.8%) presented with various joint deformities. Small joints of hands were most commonly involved. Conclusion: The joint involvement in rheumatoid arthritis is quite extensive. The disease should be diagnosed at an early stage for proper management and to prevent complications.